Time and frequency domain assessment of heart rate variability in patients with pulmonary sarcoidosis - Mari, Pier-Valerio; Melita, Veronica; Coppola, Angelo; Siciliano, Matteo; Macagno, Francesco; Pasciuto, Giuliana (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: The association between sarcoidosis and autonomic dysfunction is demonstrated but poorly known. Heart rate variability (HRV) studies can provide a simple, non-invasive analysis of sympathetic and vagal tone in sarcoidosis. To date, the burden of steroid treatment on HRV has not been investigated. We aim to compare the HRV in sarcoidosis with general population and to explorate the burden of steroid treatment in HRV. Methods: Prospective analysis of 30 patients enrolled in Sarcoidosis Clinic of Policlinico Gemelli Hospital compared to 72 healthy control subjects. Continuous EKG recording over 24 hours has been performed and HRV was assessed using time and frequency domain analysis. Results were evaluated using a propensity score matching 1:1. Results: Patients affected by sarcoidosis presented a mean age of 59.7±10.1 y and female gender predominance (n=20, 71.4%) %) while the control group was 54.6±16.0 y. The HRV analysis outlined a remarkable difference when both time / frequency domain were compared to the general, healthy population (ΔSDNN: 89.4±6.7 p=0.0001; ΔrMSSD: 5.7±2.6 p=0.03; ΔLF: 497.0±142.3 p=0.0007; ΔHF: 325.0±159.5 p=0.0442) suggesting a significant impact of sarcoidosis in autonomic activation. Remarkably the lung function tests and scadding stage did not show any relationship with the HRV (p=NS). At the same time, steroid treatment of ≥10 mg/day of prednisone for the previous 3 months was associated with a significant reduction of HRV in time (SDNN: Δ17.2±6.9, p=0.020) and frequency domain (LF: Δ355.2±125.7, p=0.009 and HF: Δ116.2±65.2, p=0.087). Lastly, the propensity score matching did confirm the previous results regarding time/frequency domain analysis. Conclusions: HRV is an effective tool for the autonomic evaluation in patients affected by sarcoidosis. The time (r-MSSD, SDNN, pNN50%) and frequency domain (HF/LF mean) analysis in sarcoidosis suggested that autonomic dysfunction is not related to the lung function or scadding stage though steroid treatment may impact.